PERBEDAAN KELUHAN SUBJEKTIF LOW BACK PAIN ANTARA PEKERJA BAGIAN KANTOR, PRODUKSI, DAN GUDANG DI PT X JAWA TENGAH - Prisma Winda Aliffia; Evi Widowati (Jurnal Kesehatan Masyarakat (Undip), 2022)
Low Back Pain (LBP) is categorized as one of the main causes of disease burden that contributes to the economic burden in terms of health system costs, lost working days, decreased productivity, and increased disability in workers. This study aims to determine the differences in subjective low back pain complaints among office, production, and warehouse workers at PT X Central Java. This research is analytic observational with a cross-sectional approach. The population in this study were female workers in the office, production, and warehouse divisions at PT X Central Java. The sample is 56 people. The instruments used are questionnaires, VAS measurement scale, REBA, and RULA assessment sheets. The results of this study are there are differences in subjective LBP complaints between office and production work activities (p=0.000), between the office and warehousing work activities (p=0.003), and between production and warehousing work activities (p=0.008). The conclusions of this study are there are differences in subjective LBP complaints among office, production, and warehouse workers at PT X Central Java. The most subjective LBP complaints and the average value of the highest degree of pain were found in the production division, which was 6.3 (moderate pain).